Utilization of Sea Cucumber (Holothuria scabra) for Nutritious and Healthy Food Consumption in the Maluku Community - Tuaputty, Hasan; Leiwakabessy, Fredy; Wael, Syahran (Universitas Pattimura, 2025)
Types of sea cucumbers consumed by communities in the Maluku region are primarily Bohadschia bivittata, Holothuria scabra, and Pentamera calcigera, which are found in sandy substrates, hence referred to as